Epidemiology of injury in skateboarding - Hunter, J. (Epidemiology of injury in adventure and extreme sports, 2012)
The purpose of this report is to review the available literature to provide an epidemiological overview of skateboarding injuries, as well as to suggest possible areas for future research. A literature search was performed with the databases of PubMed, Sport Discus, Google and Google Scholar using the search terms `skateboard`, `skateboarding`, `injury` and `injuries`, with all articles published in refereed journals in the English language being considered. An ancestry approach was also used. Articles from non-juried journals were also infrequently included to provide anecdotal information on the sport. Comparison of study results was compromised by the diversity of different study populations and variability of injury definitions across studies. The majority of injuries affect young males although conflicting arguments arise over the issues of age and experience in relation to injury severity. Most injuries are acutely suffered, and the most commonly affected body part was the wrist and forearm, with lower leg and ankle injuries also common. The incidence was relatively high but reports on severity differed. Clear conclusions could not be drawn on environmental location and risk factors. Most injuries tend to occur from a loss of balance leading to a fall, in more recent times due to a failed trick. Research on injury prevention is not conclusive although protective equipment and skatepark use are recommended. Further research using more rigorous study designs is required to gain a clearer picture of the incidence and determinants of injury, and to identify risk factors and viable injury countermeasures.